Digital Trends in Religious Advertising: Commodification of Umrah Hadiths on Instagram in the Context of Hajj and Umrah Marketing - Ali, Sitti Asiqah Usman; SM, Andi Mujahidil Ilman; A, Muh. Awaluddin; Bahri, Syamsul (Ulumuna, 2025)
This research explores the commodification of the Prophetic tradition (hadiths) regarding umrah as a marketing strategy employed by hajj and umrah travel agencies on Instagram in South Sulawesi and uncovers the patterns of commodification and the integration of authoritative religious figures. This qualitative study analyzes the contents of Instagram posts from travel agencies with over 2,000 followers registered by the Ministry of Religion. The study applies Pattana Kitiarsa's commodification theory and the Theory of Reasoned Action to analyze how religious messages are adapted to serve marketing objectives. The findings reveal three primary patterns of hadith commodification: leveraging authoritative figures to enhance credibility, interpretating hadiths to align with marketing goals, and maximalizing inspirational messages to attract customers. These strategies align with Reasoned Action Theory, highlighting perceived benefits and social influence in consumer decision-making. This study offers a unique contribution by focusing on the commodification of sacred texts in the digital marketing realm, particularly in Indonesia's Islamic travel sector. The implications underscore the importance of establishing ethical guidelines for integrating religious content into marketing, while also providing marketers with valuable insights into responsibly engaging with religious audiences.